Pengaruh Penggunaan Limbah Air Cucian Beras terhadap Pertumbuhan Tanaman Seledri (Apium graveolens L.) dengan Sistem Penanaman Hidroponik - Astija Astija; Anita Anita (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Rice washing water waste is the result of community waste which in general is no longer used, even though the waste can still be processed and used, one of which is as fertilizer for plants. Therefore, this study aims to determine the effect of the use of rice washing water waste on increasing the growth of celery (Apium graveolens L.) with a hydroponic planting system. The research location is in the Laboratory and Green House of the Biology Education Study Program, FKIP, Tadulako University. The study was carried out experimentally with a completely randomized design (CRD), which consisted of 4 types of treatment and was repeated 4 times. The treatments consisted of: K0 (control) = 0% without giving rice washing water; K1 = 25% of rice washing water waste; K2= 50% of rice washing water waste; and K3 = 75% rice washing water waste. The data obtained were then analyzed using the ANOVA test and a further BNT test was carried out which was processed using the SPSS 25 program. The results showed that the height of celery plants at the age of 10 DAP (Days After Planting), 20 DAP, and 30 DAP, was significantly affected by the treatment. rice washing water waste, although the concentrations were not significantly different between treatments. These results indicate that rice washing water has a significant effect on increasing the growth of celery plants.